Randomized controlled trial on the effects of mindfulness-based respiratory decompression therapy in claustrophobic patients undergoing MRI inspection - Zhou, Yi; Cao, Yanqing; Xu, Shan; Li, Sijin; Liang, Yidan; Zhang, Wei; Xiao, Yunping (Frontiers in Medicine, 2023)
Background Claustrophobia is a psychological disease. It is estimated to occur in 2.1–14.3% of all magnetic resonance imaging (MRI) examinations. Mindfulness decompression is an effective means to treat and reduce fear and anxiety. There is a rare report on the application of mindfulness-based stress reduction therapy in the magnetic resonance examinations of patients with claustrophobia to date. Purpose The purpose of this study is to explore the intervention effect of mindfulness respiratory decompression therapy on the MRI inspection of patients with claustrophobia. Methods A total of 86 patients with claustrophobia requiring MRI in our hospital from January 2018 to December 2020 were divided into two groups. The control group was given routine psychological nursing, and the observation group was given a mindfulness breathing technique on the basis of the control group. Before and after the intervention, we compared the intervention effect, satisfaction with nurses’ psychological intervention technique, severe autonomic nervous symptoms during the examination, self-rating anxiety scale (SAS) scores, and profile of mood states revised (POMS-R) scores. Results The total effective rate of intervention in the observation group was 90.90%, which was significantly higher (χ2 = 6.857, p = 0.00004) than that in the control group (26.19%). Severe autonomic nervous symptoms in the observation group were significantly lower than those in the control group (p < 0.05). After the intervention, SAS scores and POMS-R scores in the observation group decreased with statistical significance (p < 0.05). Conclusion Mindfulness respiratory decompression therapy can effectively help claustrophobic patients complete an MRI examination, which may be worthy of wide promotion and application in the clinic.